Teacher-student relationship, coping style and sports anxiety among middle school students: a situational study based in Shanghai - Qi, Jiatian; Li, Jingjing; Liu, Bing (Frontiers in Psychology, 2025)
ObjectiveThe present research aims to explore the relationship between coping style, teacher-student relationship, and sports anxiety among middle school students.MethodsA total of 289 Chinese middle school students from three schools in Shanghai participated in the survey.Results(1) A negative teacher-student relationship significantly affects sports anxiety, and conversely, sports anxiety significantly impacts the negative teacher-student relationship, demonstrating a strong mutual effect; (2) Both active coping style and negative coping style significantly influence sports anxiety, while sports anxiety also significantly affects active coping style among middle school students. In the two-way model of teacher-student relationship (including positive and negative dynamics) and sports anxiety, the mediating effect of coping style is not significant.Conclusion and perspectiveThis study enhances our understanding of the roles of student-teacher relationship and sports anxiety, providing a concrete sample and example for educational authorities in developed countries to identify relevant issues in the field of physical education.